The importance of local advantages and productive services in asian automotive industries in São Paulo state: the case of Piracicaba, Indaiatuba and Sumaré - Takami, Saulo Teruo; Mendes, Auro (Sociedade & Natureza, 2017)
The industrial activity, mainly at automotive sector, after the 1970s, started to demand, increasingly, productive services since simple activities, such as: safety, cleanliness, food, for instance, until sophisticated services (marketing, design, computer, among others). This kind of service involves a group of activities that may be intensive in capital, technology and highly skilled labour. The implantation of Hyundai in Piracicaba city, in 2012; Toyota in Indaiatuba city, in 1998 and Honda in Sumaré city, in 1997, reveals the importance of countryside of São Paulo state in attraction of Asian industries. The present paper has the objective to analyse the importance of local advantages and productive services at Asian industries in mentioned cities that represent the spatial area of this research. Besides the introduction and final considerations, this paper will deal the conceptual aspects and the typology of services to industrial activity; the importance of local advantages to Asian automotive industries in São Paulo state and the relevance of productive services and other locational factors to automotive industries researched.